2014
DOI: 10.1136/oemed-2013-101960
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of hairdressers to ortho- and meta-toluidine in hair dyes

Abstract: BackgroundCarcinogenic aromatic amines derived from hair dyes have recently received new attention. One of these is ortho (o)-toluidine, which is classified as carcinogenic to humans.ObjectivesTo clarify exposure of hairdressers to potentially carcinogenic aromatic amines, including o-toluidine.MethodsWe measured eight potentially carcinogenic aromatic amines in the blood of 295 hairdressers, 32 users of hair dyes and 60 controls. The study was restricted to female non-smokers. Lifestyle data were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Its carcinogenic power is probably due to the ability to determine the formation of DNA adducts, causing damage to the DNA structure. Therefore, O-toluidine is classified in group A [220][221][222][223][224][225][226][227][228][229] .…”
Section: Ortho-toluidinementioning
confidence: 99%
“…Its carcinogenic power is probably due to the ability to determine the formation of DNA adducts, causing damage to the DNA structure. Therefore, O-toluidine is classified in group A [220][221][222][223][224][225][226][227][228][229] .…”
Section: Ortho-toluidinementioning
confidence: 99%
“…Laboratory and medical staff may be exposed when using it for staining tissues (295,296). Other possible exposure may result from the use of certain hair dyes, the local anesthetic prilocaine and tobacco smoke (297,298). …”
Section: Resultsmentioning
confidence: 99%
“…Aromatic amines are commonly used in hair dye formulations, although classified carcinogenic aromatic amines have been excluded [Bolt and Golka, 2007]. In a previous study on Swedish hairdressers we found evidence of exposure to aromatic amines, including the human bladder carcinogen orthotoluidine, based on measurements of hemoglobin adducts [Johansson et al, 2015]. Studies have shown that hair dye product on the market today can induce chromosome damage, such as micronuclei or strand breaks [Cavallo et al, 2005;Espinoza et al, 2008].…”
Section: Introductionmentioning
confidence: 94%
“…The study population was described in detail previously [Johansson et al, 2015]. We recruited 295 hairdressers who had worked as a hairdresser for at least 6 months and 92 non-hairdressers, which included 60 controls who had never used any hair dye in the last 12 months and 32 consumers who had used hair dye on a regular base (about every 8 weeks).…”
Section: Study Participantsmentioning
confidence: 99%